2018
DOI: 10.1074/jbc.ra118.004510
|View full text |Cite
|
Sign up to set email alerts
|

The human gut microbe Bacteroides thetaiotaomicron encodes the founding member of a novel glycosaminoglycan-degrading polysaccharide lyase family PL29

Abstract: Edited by Chris WhitfieldGlycosaminoglycans (GAGs) and GAG-degrading enzymes have wide-ranging applications in the medical and biotechnological industries. The former are also an important nutrient source for select species of the human gut microbiota (HGM), a key player in host-microbial interactions. How GAGs are metabolized by the HGM is therefore of interest and has been extensively investigated in the model human gut microbe Bacteroides thetaiotaomicron. The presence of as-yet uncharacterized GAG-inducibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 38 publications
0
31
1
Order By: Relevance
“…BT3331 susD demonstrated a very strict substrate specificity binding only to CS-A with a measurable affinity, similar to that of BT3329 SGBP (Supplementary Table 1). The surface lyase, BT3328 PL29 , showed its highest enzymatic activity and affinity against CS-A > CS-C > HA and little activity on DS, differing from previous data 18 . End point assays, the total number of glycosidic bonds cleaved, followed the relationship of HA > CS-C > CS-A ( Fig.…”
Section: Resultscontrasting
confidence: 92%
See 1 more Smart Citation
“…BT3331 susD demonstrated a very strict substrate specificity binding only to CS-A with a measurable affinity, similar to that of BT3329 SGBP (Supplementary Table 1). The surface lyase, BT3328 PL29 , showed its highest enzymatic activity and affinity against CS-A > CS-C > HA and little activity on DS, differing from previous data 18 . End point assays, the total number of glycosidic bonds cleaved, followed the relationship of HA > CS-C > CS-A ( Fig.…”
Section: Resultscontrasting
confidence: 92%
“…Bacteroides culture and genetic manipulation: Various Bacteroides strains and B. theta VPI-5482 were cultured anaerobically in a Whitley A35 Workstation (Don Whitley) at 37°C in either tryptone yeast extract glucose medium or minimal medium (MM) containing GAGs (described below). B. theta strains containing specific gene deletions or inactivated versions of enzymes were made by counter selectable allelic exchange as described below 18 . All genetic mutants, except Δbt3328, were provided by Dr Guy E. Townsend and Prof. Eduardo Groisman 13 .…”
Section: Methodsmentioning
confidence: 99%
“…Two types of enzymes that cleave glycosidic bonds in the CAZymes database include GHs and PLs (El Kaoutari et al., 2013), which may be used to cleave the glycosidic bonds of SPs (Cartmell et al., 2017; Cockburn & Koropatkin, 2016). Notably, endogenous host HS and CS have been confirmed to be degraded by PLs belonging to families PL‐8, PL‐12, PL‐13, and PL‐29 (El Kaoutari et al., 2013; Ndeh et al., 2018). With regard to the distribution of CAZymes in the gut microbiota, Bacteroidetes encode 137.1 CAZymes per genome on an average, whereas Firmicutes only encode 39.6 CAZymes per genome (El Kaoutari et al., 2013).…”
Section: Sps and Gut Microbiotamentioning
confidence: 99%
“…Sugiura et al identified two highly homologous occlusion-derived variants of virus envelope protein 66s from Autographa californica nucleopolyhedrovirus and Bombyx mori nucleopolyhedrovirus, and both of the variants showed specific lyase activity towards non-sulfated and 6-O-sulfated CS (Sugiura et al, 2011;Sugiura et al, 2013). BtCDH from the human gut microbe Bacteroides thetaiotaomicron belongs to a new PL family (PL29) and shows optimum endolytic activity toward HA and CS, particularly large chains longer than decasaccharide, at a very high temperature of 60 • C (Ndeh et al, 2018). Two novel CS/DS lyases have been found from Acinetobacter sp.…”
Section: Newly Identified Cs/ds Lyasesmentioning
confidence: 99%